A companion to Sardinian history, 500-1500 - Hobart, Michelle (Brill, 2017)
The first English-language survey of medieval and modern Sardinia, this volume offers access to long-awaited European scholarship on a critical missing link in the Mediterranean. Based on new archaeological fieldwork and current research from a variety of academic perspectives - architecture, colonialism, ecclesiastic history, cartography, demography, law, musicology, politics, trade, and urban planning - the authors provide the foundation to incorporate Sardinia into a broader European history. Among other contributions, archaeology adds critical insight into the relationship between Christian, Muslim, and Jewish inhabitants of Sardinia, through examinations of urban and rural settlement patterns. This volume aims to stimulate further analysis of the critical role Sardinia has played as one of the largest and most strategically located islands in the Mediterranean
Description based on print version record
Keywords: Geschichte 500-1500; Geschichte; Italien; Sardinien; Sardinia (Italy) / History / 456-1297; Sardinia (Italy) / History / Aragonese and Spanish rule, 1297-1708; Italy / Sardinia; 456-1708; History; Aufsatzsammlung